Effect of loop gain of ripple cancellation converter on twice‐line‐frequency voltage ripple in PFC converter. Issue 13 (1st June 2017) - Cai, Yaping; Xu, Jianping; Liu, Gao; Yao, Zhanhui; Zhou, Guohua
Abstract : Power factor correction (PFC) converter with a twice‐line‐frequency ripple cancellation converter (RCC) has attracted much attention due to its ability of twice‐line‐frequency output voltage ripple cancellation and high power conversion efficiency. The audio susceptibility of buck‐type RCC operating in discontinuous conduction mode is derived and the effect of loop gain of RCC on the cancellation of twice‐line‐frequency output voltage ripple is studied. Experimental results of a 50 W prototype are presented to verify the analysis results.